Menikah untuk Diceraikan: Menyorot Hak-Hak Perempuan pada Isbat Nikah untuk Cerai di Pengadilan Agama Medan Tahun 2015-2017 - Yazid, Imam (Al-Manahij: Jurnal Kajian Hukum Islam, 2019)
The validity of marriage in Indonesia is regulated through Islamic law and regulations in Indonesia. In fact, many marriages occur that do not meet the regulations in Indonesia, resulting in legal uncertainty of the people involved in the marriage. This research is empirical legal research. The purpose of this study is to find out how the policies of the Religious Courts in Medan settles cases of iṡbat nikah (seeking a formal, legalized marriage certificate) that aims to divorce in 2015-2017, how are legal considerations in giving a decision to isbat nikah that aims to divorce, and how is legal certainty after divorce through isbat nikah. This research found that: firstly, isbat nikah is a solution to the problem of a married couple who are not recorded by an official appointed by the state and then the marriage certificate is to establish a divorce permit; secondly, religious court judges in Medan have a legal basis in giving a decision of isbat nikah cases to divorce, so the decision can be normatively accounted for; thirdly, the court’s decision gives rise to the benefits desired by the Shari'a, namely legal certainty after the isbat nikah, namely, among others, the provision of appropriate mut’ah (severance pay) to ex-wives, provision of living expenses for children who are not yet 21 years old, and formal registration of children from marriages that are not recorded by officers appointed by the state when the previous marriage occurred.